Plant secondary metabolites against Candida auris: mechanisms and evidence - Holanda de Sousa, Silvana; Ferreira Sousa, Odaiza; Cardoso Jurema, Halline; Silva Campos, Thales Guilherme; León Rodríguez , Cesar Elías; Pantoja Soares da Silva , Marília; Silva , Vitória Beatriz; Rodrigues Cangussu, Alex Sander; de Souza Aguiar , Raimundo Wagner; Rodrigues dos Santos, Gil; Gontijo da Silva, Marcos (Revista de Ciencias Agrícolas, 2026)
Candida auris is an emerging multidrug-resistant fungal pathogen that poses a significant public health threat. This fungus has spread to more than 30 countries. This review was conducted aiming to search for in vitro studies on the antifungal actions of plant metabolites against C. auris. The review was constructed following the guidelines of the PRISMA statement. The research protocol was registered on the PROSPERO platform. A literature search was performed in the PubMed, Scopus, and Virtual Health Library databases, with no restrictions on year or language. Eligibility criteria were based on the PICO concept. Data were meta-analyzed using R software. The risk of bias assessment was performed using an adaptation of the CONSORT tool. A total of 11 of the 768 articles were included in the systematic review and meta-analysis, and 30 secondary metabolites of plant origin were analyzed. Of the 30 metabolites found, 26 presented results similar to the controls, and 4 showed superior results: palm leaf extract, Syzygium samarangense bark, Cinnamomum zeylanicum oil (bark) and Cinnamomum zeylanicum (leaf). Most plant secondary metabolites showed excellent antifungal potential against C. auris. As a limitation of the study, metabolites of very heterogeneous origin, extraction method, and distinct controls were grouped, which may have interfered with the interpretation of the results, increasing the risk of bias and imprecision. Therefore, further research is needed to confirm their clinical efficacy and safety and elucidate the mechanisms of action.